2002
DOI: 10.1021/jf011457a
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity of Isobutylamides Identified in Piper nigrum Fruits against Three Mosquito Species

Abstract: The insecticidal activity of materials derived from the fruits of Piper nigrum against third instar larvae of Culex pipiens pallens, Aedes aegypti, and A. togoi was examined and compared with that of commercially available piperine, a known insecticidal compound from Piper species. The biologically active constituents of P. nigrum fruits were characterized as the isobutylamide alkaloids pellitorine, guineensine, pipercide, and retrofractamide A by spectroscopic analysis. Retrofractamide A was isolated from P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 20 publications
(23 reference statements)
5
119
1
7
Order By: Relevance
“…This difference was likely associated with differences in the methods used to obtain the extract (21) (31) (32) . The lack of standardization hampers the comparison between different piperine content rates; however, Ik and colleagues have found LC 50 values of 3.21ppm for isolated piperine (33) , which is similar to the LC50 determined for PnE containing only 60% piperine. These fi ndings indicate that PnE activity cannot be attributed solely to piperine but also to other isobutylamide compounds found in this species such as retrofractamide A and pellitorine, piperine derivatives that have shown LC 50 values of 0.028ppm and 0.86, respectively (34) .…”
Section: Discussionmentioning
confidence: 51%
“…This difference was likely associated with differences in the methods used to obtain the extract (21) (31) (32) . The lack of standardization hampers the comparison between different piperine content rates; however, Ik and colleagues have found LC 50 values of 3.21ppm for isolated piperine (33) , which is similar to the LC50 determined for PnE containing only 60% piperine. These fi ndings indicate that PnE activity cannot be attributed solely to piperine but also to other isobutylamide compounds found in this species such as retrofractamide A and pellitorine, piperine derivatives that have shown LC 50 values of 0.028ppm and 0.86, respectively (34) .…”
Section: Discussionmentioning
confidence: 51%
“…For example, because piperine is an amide that lacks the isobutyl substituent. the previous studies have suggested the presence of several other bioactive compounds in P. nigrum; such compounds could include the isobutylamides retrofractamide A, pipercide, guineensine and pellitorine (Park et al, 2002).…”
Section: Aedes Aegypti Larvae Lethality Bioassays and Chromatographicmentioning
confidence: 97%
“…Acetogenins act as pesticides on several arthopodes what is based on a specifi c mechanism that blocks energy generation in the mitochondrial complex I. Another species, Piper nigrum L., Piperaceae, which is commonly used as black pepper, contains a series of amides also possessing insecticidal potential such as piperine, pipercide, guineensine, pellitorine, pipgulzarine and pipzorine (Park et al, 2002;Siddiqui et al, 2004;Siddiqui et al, 2003). Ilex paraguariensis A.…”
Section: Introductionmentioning
confidence: 99%
“…Este conjunto de substâncias pode ser dividido em dois: amidas que possuem a parte relativa ao ácido carboxílico originada da rota biossintética mista (ácido chiquímico/policetídica, 1 a 6) 52,53,54 e as amidas que têm esta parte da molécula originada diretamente de ácidos graxos (substâncias 7 a 9). 51,52,54 Estas rotas coocorrem, visto que ambos os tipos foram obtidos da mesma planta. O nitrogênio da amida, nestes compostos, é substituído pelo grupo isobutila (2, 4 a 8), além de piperidina (1 e 3) e por um homólogo de isobutila (9).…”
Section: Produtos Naturais De Origem Vegetal Com Atividade Larvicidaunclassified